Functional Aspects and Physiotherapy Education in Home Between Intra- and Extra-Capsular Femoral Fractures of Hospitalized Elderly - Lanzotti, Humberto; Armond, Jane de Eston; Ribeiro, Ana Paula (International Journal of Orthopedics and Rehabilitation, 2019)
Objective: To verify the intra- and extra-capsular femoral fracture, the degree of dysfunction that the elderly patient presents in the postoperative period, and the care they receive at hospital discharge. Design/Setting: This was a prospective cross-sectional study conducted elderly patients hospitalized for proximal femoral fractures who received clinical and surgical care in a public hospital. Participants: Twenty-five elderly patients with femoral fractures: intra capsular (GFI; n=11) and extra-capsular (GFE; n=14). Main Outcome Measures: Questionnaire to the postoperative clinical aspects was performed. The angle joint of the lower limbs was determined by goniometer and the foot functionality by Foot Function Index (FFI) questionnaire. The pain was evaluated using the visual analogue pain scale (VAS) and muscle strength by the force scale. Results: A greater female predominance was observed for GFI group. Regarding home guidelines, both groups of fractures did not present reports by the health professionals involved. The range of motion remained reduced for hip adduction and ankle dorsiflexion in GFE group. The GFI group reduced flexion and extension knee and the functionality of the feet. Conclusions: It can be concluded that proximal femoral fractures intra- and extra-capsular, differ according to gender, with a female predominance of intra-capsular fractures. As well, regarding the range of joint motion, the extra-capsular fractures resulted in reductions in hip adduction and ankle dorsiflexion compared to intra-capsular fractures, which presented reductions in knee flexion and extension. Regardless of the type of fracture, there was no home guidance after the surgical procedure.